Desenvolvimentos da biopolpação no Brasil - Ferraz, André [UNESP] (My University, 2007)
Biopulping is a technology which application can be advantageous to mechanical or chemical pulping. It presents benefits such as the creation of stronger pulp, as well as energy or chemicals savings. This paper gives an overview of the recent efforts to develop biopulping processes in Brazil as well as provides critical information on biopulping development worldwide. Eucalyptus grandis wood chips have been biotreated by Ceriporiopsis subvermispora in a 50-ton biopulping pilot-plant and used to produce TMP and CTMP pulps on a mill scale, Up to 18% and 27% energy savings have been observed for producing 450-470 CSFreeness TMP and CTMP pulps. Despite darker bio-TMP pulps are produced, one-stage bleaching with 5% H2O2 was sufficient to improve brightness values to 70% and 72% for bio-TMP and control pulps, respectively. Understanding biopulping mechanisms is also relevant because more resistant and competitive fungal species could be selected with basis on a function-directed screen-ing project. As far as the chemical changes induced by the fungus in wood are concerned, recent efforts have pointed out for two different types of wood transformations. One of them involves intense lignin depolymerization in short biotreatment periods, while the other indicates that esterification reactions of oxalate secreted by the Jungas on the polysaccharides chains increase the water saturation point of the fibers. Both transformations are expected to affect the fiber-fiber bonding and, consequently, the physical resistance of wood.
Biopulping developments in Brazil
Keywords: Biopulping; Cellulose; Lignin; Pulp and paper; Wood biodegradation; Bleaching; Brazil; Chemical pulp; Paper and pulp industry; Biotreatment periods; Fiber-fiber bonding; Biodegradation; Lignins; Pulp Industry; Pulping